Pengaruh Kampanye Produk Telepon Cerdas “Hollywood in Your Pocket” Pada Iphone 13 Pro Terhadap Keputusan Beli Konsumen: Survei di Sebuah Kampus di Jakarta Selatan - Fadilah, Ramadan Faqih (Brand Communication, 2023)
In this era of globalization, technology is increasing and developing with the times. Technological advances also have a positive impact on the ease of accessing information digitally. Nowadays, smartphones are very much needed by all individuals. With the sophistication of a smartphone, we can find information, communicate and many other benefits. One of the most well-known smartphone companies today is Apple. At first, Apple started its company with computer production. Apple was founded on April 1, 1976, by Reed University students, namely Steve Jobs and Steve Wozniak. In September 2021, Apple released the iPhone 13 with a new feature that the previous iPhone generations didn't have. This feature is a cinematic mode. Can produce bokeh effects automatically, the cinematic mode feature gives a cinematic impression in the style of Hollywood films.This feature can be used in the camera application, then switch to cinematic mode. All of these features are explained in the “Hollywood in Your Pocket” campaign. This study aims to see the effect of the "Hollywood in Your Pocket" campaign on purchasing decisions by using quantitative research methods. The sampling technique used was explanatory research with 100 respondents who were students of Pancasila University. The results of the study show that there is an influence between the "Hollywood in Your Pocket" campaign on purchasing decisions of 36.5%. Suggestions from researchers are that further research can be carried out using qualitative methods to gather information from sources who have competence related to digital campaigns.